2019
DOI: 10.1111/jpm.12574
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and providers' experiences with video consultations used in the treatment of older patients with unipolar depression: A systematic review

Abstract: Patients' and providers' experiences with video consultations used in the treatment of older patients with unipolar depression: a systematic review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(88 citation statements)
references
References 47 publications
4
84
0
Order By: Relevance
“…Studies have identified a number of benefits and challenges in association with adopting telepsychiatry (Chakrabarti 2015; Christensen et al . 2020; Scott Kruse et al . 2018), and technical challenges were a prominent theme in several studies (Christensen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified a number of benefits and challenges in association with adopting telepsychiatry (Chakrabarti 2015; Christensen et al . 2020; Scott Kruse et al . 2018), and technical challenges were a prominent theme in several studies (Christensen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Very few qualitative studies have investigated VC usage among older adults with depression, and, of these, most are characterized by methodological limitations and deficiencies, and they rarely include both patient and provider perspectives (Christensen et al . 2020). It is apparent that significant gaps exist in the literature in relation to the adoption of VC for older people with depression conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation outcomes were reported in 8 reviews (20,22,25,26,31,(33)(34)(35) Relevant outcomes included assessment comparability (K=2), fidelity to intervention and competence of therapists (K=1) (34), patient adherence to intervention (K=3) (20,26,31), patient attendance (K=4) (31,(33)(34)(35), safety (K=2) (26,34), and technical difficulties (K=3) (26,34,35).…”
Section: Implementation Outcomesmentioning
confidence: 99%
“…Acceptability outcomes were reported in 10 reviews (18,20,21,26,27,(31)(32)(33)(34)(35). Relevant outcomes included clinician satisfaction (K=5) (18,20,21,32,34) , therapeutic alliance (K=6) (21,26,27,(33)(34)(35), patient satisfaction (K=7) (20,21,(31)(32)(33)(34)(35) and convenience (K=3) (21,33,35).…”
Section: Acceptability Outcomesmentioning
confidence: 99%
“…6 Another review of telepsychiatry for geriatric patients found that it supports mental health practice, especially when face-to-face therapy is not possible. 7 The main drawbacks were technical problems and lack of support from staff.…”
Section: Emergency Departments (Eds) Using Telepsychiatry For Psychimentioning
confidence: 99%